Investigations on the corrosion of constructional steels in different aqueous and simulated atmospheric environments - D. Gassama; A. A. Diagne; I. Yade; M. Fall; S. Faty (Bulletin of the Chemical Society of Ethiopia, 2015)
The corrosion behavior of three constructional steels used in Senegal, S235, S275 and S355, was studied in simulated atmospheric conditions in an exposure chamber above distilled water and above 3% NaCl solution representing marine atmosphere by comparing the ratio of rusted to unrusted area. Electrochemical test methods (potentiodynamic tests and electrochemical impedance spectroscopy) were employed to study the steels fully immersed in acidic, near neutral and basic conditions in 0.5 M HCl, NaCl, and NaOH solutions, respectively. Results indicate that S355 and S235 steels have comparable corrosion resistance, which are much lower than that of S275.